International health care reform : a legal, economic, and political analysis - Flood, Colleen M. (London ; New York : Routledge, 2000)
This book analyses the wave of competition-oriented reform by comparing ""internal market reform"" (proposed in publicly-funded health care systems) with ""managed competition reform"" (proposed in systems with a mixture of public/private financing) and the role of ""managed care"" in each of these reform theories. International Health Care Reform clearly explains the arguments in economics and justice for intervention by governments in health care markets; the structure and dynamics of health care systems; and the features of competition-oriented reform models. The book will app
1. Introduction -- 2. Arguments in economics and justice for government intervention in health insurance and health service markets -- 3. The reform of health care allocation systems in the US, The Netherlands, New Zealand, and the UK -- 4. Accountability of health care service purchasers : comparing internal markets and managed competition -- 5. The interface between health care service purchasers and providers : contracting out versus integrated production -- 6. The problems of monopoly supply -- 7. Achieving quality in a competition-oriented system -- 8. Conclusion.
Includes bibliographical references (pages 287-307) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Health care reform -- Cross-cultural studies; Cross-cultural studies; Health Care Reform -- trends; Cross-Cultural Comparison; Services de santé -- Réforme -- Études transculturelles; Services de santé -- Réforme -- Études transculturelles; Études transculturelles; HEALTH & FITNESS -- Health Care Issues; MEDICAL -- Public Health; MEDICAL -- Health Policy; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Diseases; MEDICAL -- Health Care Delivery; Cross-cultural studies; Health care reform; Gezondheidszorg; Hervormingen; Economische aspecten; Juridische aspecten; Politieke aspecten; Electronic books; dissertations; Cross-cultural studies; Academic theses; Thèses et écrits académiques.